2006
DOI: 10.1001/archpsyc.63.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality in Pediatric Patients Treated With Antidepressant Drugs

Abstract: Use of antidepressant drugs in pediatric patients is associated with a modestly increased risk of suicidality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
593
3
25

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 913 publications
(637 citation statements)
references
References 12 publications
16
593
3
25
Order By: Relevance
“…Looking at the method for suicide, the decline in suicide by overdosing with medications may be related to the introduction of less toxic antidepressant medication such as the selective serotonin reuptake inhibitors (although some authors have indicated that the use of antidepressant drugs in pediatric patients is associated with a modestly increased risk of suicidality [12]). The use of more lethal suicide methods by girls in recent years may be a product of changes in cultural patterns that allow girls and women in general to hold similar roles in contemporary Italy as their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the method for suicide, the decline in suicide by overdosing with medications may be related to the introduction of less toxic antidepressant medication such as the selective serotonin reuptake inhibitors (although some authors have indicated that the use of antidepressant drugs in pediatric patients is associated with a modestly increased risk of suicidality [12]). The use of more lethal suicide methods by girls in recent years may be a product of changes in cultural patterns that allow girls and women in general to hold similar roles in contemporary Italy as their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Such work is important in mood and anxiety disorders, given emerging data on amygdala function in these conditions (6,12), coupled with questions surrounding therapeutics. For instance, it is unclear why youth show a different pattern of responses to antidepressant medications, including a possible increased risk of suicidal ideation, than adults (19). Similar questions have emerged about CBT, as one recent study in adolescent MDD found that CBT alone showed no advantage over pill-placebo, but CBT was helpful when combined with fluoxetine (20).…”
mentioning
confidence: 99%
“…Independent review of adverse events from data from 24 placebo-controlled trials of AD use in children and adolescents found that suicidality significantly increased with SSRI treatment compared to placebo, leading the FDA to issue a “black box” warning (see Brent, 2004; Goodman et al , 2007; Newman, 2004). Additional studies have likewise found evidence of increased suicidality with use of SSRIs in juveniles, suggesting that there may be an unfavorable risk to benefit ratio for SSRIs (with fluoxetine as a possible exception) (Bailly, 2008; Barbui et al , 2009; Bridge et al , 2007; Cipriani et al , 2005; Doggrell, 2005; Fergusson et al , 2005; Goodman et al , 2007; Hammad et al , 2006; Laughren, 2006; Mosholder and Willy, 2006; Olfson and Marcus, 2008; Olfson et al , 2006; Richmond and Rosen, 2005; Ryan, 2005; Scahill et al , 2005; Tiihonen et al , 2006; Vitiello and Swedo, 2004; Whittington et al , 2004; Wohlfarth et al , 2006). Many of these and other studies have pointed out difficulties in interpretation of the data and have stated that there is considerable risk for suicidality if pediatric patients are not adequately treated (e.g., Bridge et al , 2007; Mann et al , 2006).…”
Section: Discussionmentioning
confidence: 99%